(untitled) (Swiss Medical Weekly, 2022)
BACKGROUND: Coronavirus disease 2019 (COVID-19) can be more severe in infants than in older children. To date, only a few case series have reported data on neonates with COVID-19, including mostly asymptomatic neonates who were tested because of exposure to maternal SARS-CoV-2 infection. This study summarises nationwide epidemiological data, clinical characteristics, treatment and outcomes of neonates presenting with symptomatic SARS-CoV-2 infection. METHODS: Data were prospectively collected through the Swiss Paediatric Surveillance Unit from hospitalised neonates with laboratory-confirmed SARS-CoV-2 infection (positive polymerase chain reaction on a respiratory sample) from 1 March 2020 to 31 September 2021. All 29 paediatric hospitals in Switzerland reported cases. RESULTS: In total, 73 neonates were included; 7 (10%) were preterm. The median age at presentation was 17 days (interquartile range [IQR] 11–23); 40 (55%) were female. The majority of neonates (64, 88%) were admitted from home. Nine (12%) had a pre-existing medical condition. Overall, the most common symptom recorded was fever in 52 (71%), followed by rhinorrhoea or nasal congestion in 32 (44%) and respiratory distress in 19 (26%). Twenty (27%) neonates presented with fever without a source. Seven (10%) neonates were admitted to an intensive care unit (5 for respiratory failure and 2 for monitoring). One (1%) neonate required inotropic support. The median length of hospital stay in term neonates was 4 days (IQR 3–5). Two (3%) were treated with corticosteroids and 1 (1%) with remdesivir. In total, 60 (82%) neonates had contact with a known or suspected SARS-CoV-2 index case. All of the 71 neonates for whom data were available were discharged to their homes without symptoms. CONCLUSION: In neonates, COVID-19 mainly presents with fever, and symptoms of upper and lower respiratory tract infection. The clinical course is mostly mild, requiring a short period of hospitalisation. COVID-19 needs to be added as a differential diagnosis in neonates who present with fever without a source. However, the presence of SARS-CoV-2 should not deter from the search for a serious bacterial infection. Further data from surveillance studies are needed to better understand COVID-19 in neonates, guide therapy and to evaluate whether the clinical spectrum is changing with new SARS-CoV-2 variants.